The influence of financial ratios on financial distress of transportation sector companies in Indonesia - Harnida, Mutia; Syam, Akhmad Yafiz; Syahdan, Saifhul Anuar; Ruwanti, Gemi; Boedi, Soelistijono (KINERJA, 2024)
The purpose of this research is to determine the influence of the current ratio, debt to asset ratio, debt to equity ratio, return on asset, return on equity, total asset turn over on financial distress in transportation sector companies listed on the Indonesia Stock Exchange. Using purposive sampling method, a sample of 22 companies was obtained over a period of 3 years. This research utilizes secondary data obtained from financial and annual reports published on the Indonesia Stock Exchange from 2020 to 2022. Logistic regression is employed to analyze the data. The results of this study indicate that the debt to asset ratio has a partial effect on financial distress. However, the current ratio, debt to equity ratio, return on asset, return on equity, and total asset turnover do not have a partial effect on financial distress. Simultaneously, the influence of the current ratio, debt to asset ratio, debt to equity ratio, return on asset, return on equity, and total asset turnover affects financial distress